Europe’s unheeded vocation: from reconstructive vision to counterfactual critique - Sabine Frerichs (European Law Open)
This review essay forms a contribution to the Dialogue & Debate symposium on Christian Joerges’s volume Conflict and Transformation (Hart 2022). The specific angle of this article is an interdisciplinary one that conceives of Joerges’s work as a boundary-crossing exercise between law and the social sciences. Aspects highlighted are the inspiration that his work finds in responding to Europe’s vocation, or realising the latter’s normative potential; the law-in-context quality of the approach, which combines inside and outside perspectives on what the law is and does, how it motivates and what it means; and the two-pronged ambition to take the law seriously as a legitimating force and to question, at the same time, the power of economic ‘facts’ and arguments, which sometimes overrule what seems legitimate. Moreover, this article considers the relevance and implications of two intellectual influences on Joerges’s work, one a more formative one (Habermas) and one resonating with recent experiences of crisis (Polanyi), and it follows the journey of Joerges’s reconstructive approach within European studies: between integration theory, governance approaches, and rethinking democracy in postnational constellations. As Joerges himself concedes, the normative vision that this yielded for European law and politics was overtaken by actual developments in the context of the monetary union, and conflicts-law constitutionalism became more of a counterfactual appeal. This article outlines how the critical edge of this approach could be enhanced by taking perspectives from critical political economy on board, which would also facilitate countering economic arguments.